2014
DOI: 10.1002/cpp.1937
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Therapist Attachment in Alliance and Outcome: A Systematic Literature Review

Abstract: Therapist attachment style has the potential to influence therapeutic alliance and client outcome. Improvements in therapeutic practice might be achieved if therapists have greater knowledge of their own attachment styles and how these interact with their clients' attachment styles to influence the psychotherapy relationship and outcomes. From the outset of their careers, therapists should receive training and supervision to enhance the awareness of their individual attachment experiences and how these play ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 49 publications
6
52
0
3
Order By: Relevance
“…Most notably, the fact that attachment theory is a universal theory of relationships, which applies to both voice hearers and mental health workers alike and emphasizes the functional nature of insecure attachment styles in the context of earlier relationships means that it has the potential to be less pathologizing than other models. Relatedly, attachment theory also provides a framework for conceptualizing the role of the mental health workers’ own relational histories and attachment styles within the therapeutic processes, including how these interact with those experiences and attachment patterns of voice hearers (122, 123). …”
Section: Discussionmentioning
confidence: 99%
“…Most notably, the fact that attachment theory is a universal theory of relationships, which applies to both voice hearers and mental health workers alike and emphasizes the functional nature of insecure attachment styles in the context of earlier relationships means that it has the potential to be less pathologizing than other models. Relatedly, attachment theory also provides a framework for conceptualizing the role of the mental health workers’ own relational histories and attachment styles within the therapeutic processes, including how these interact with those experiences and attachment patterns of voice hearers (122, 123). …”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic relationship is here defined as the “feelings and attitudes that therapist and client have toward one another and the manner in which they are expressed” (Norcross & Lambert, , p. 4). This broadens the narrower conceptualization of the therapeutic relationship used in previous reviews (e.g., Berant & Obegi, ; Degnan, Seymour‐Hyde, Harris, & Berry, ), which only considered literature using client and therapist ratings of the therapeutic relationship. Our broader definition encompasses relevant yet less direct indicators such as the therapist's interpersonal behavior and in‐session emotional experience, such as countertransference.…”
Section: Therapists’ Internalized Relational Modelsmentioning
confidence: 99%
“…She concluded that the unequal nature of the therapeutic relationship might favor clients’ attachment patterns over therapists’ as predictors of the alliance, or perhaps that a narrower range of attachment styles among therapists compared to their clients, makes therapist effects difficult to detect. Degnan and colleagues () regarded the evidence as sufficiently convincing to recommend that therapists take account of their attachment style within therapy. All reviews noted the interaction of client and therapist attachment styles as an area for further research.…”
Section: Therapists’ Internalized Relational Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lead and co-therapists will also complete the WAI in relation to the service user and each family member/FSM at the end of session 3. The WAI has previously been used with key workers and therapists [7476]. …”
Section: Data Collectionmentioning
confidence: 99%